Economic comparison of reference solar thermal systems for households in five European countries. (15th November 2019) - Louvet, Y.; Fischer, S.; Furbo, S.; Giovannetti, F.; Helbig, S.; Köhl, M.; Mugnier, D.; Philippen, D.; Veynandt, F.; Vajen, K.
Graphical abstract: Highlights: A methodology for calculating the heat cost of solar thermal applications is presented. Three different indicators are proposed. The methodology is applied to 11 systems in 5 European countries. Heat costs vary greatly from one country to another, but trends are emerging. Abstract: This study presents a methodology developed in the framework of Task 54 of the Solar Heating and Cooling (SHC) Program of the International Energy Agency (IEA) to calculate the heat cost per kWh final energy of solar thermal systems. Based on the concept of levelized cost of energy, three indicators are introduced depicting the heat cost of the solar part of the heating system only (LCoHsol, fin ), the conventional part (LCoHconv, fin ) or the overall solar assisted heating system (LCoHov, fin ). The LCoHov, fin enables a comparison with other heating systems using different technologies. Applied to eleven residential systems in five European countries, the results show that the heat cost differs widely, depending on countries and system types. The solar heating system raises the heat cost of the overall solar assisted heating system compared to a reference system without solar assistance (subsidies are not considered) in most studied cases, but some solar domestic hot water systems and solar heating systems for multi-family houses are close to parity under current economic conditions and the assumptions considered in the paper. This work also highlights the importance of calculating the heat cost with a standardized methodology to enable a comparison between different systems.